Antibiotic Consumption in Hospitalized Children at the University Clinic for Pediatric Diseases – Skopje - Pechijareva-Sadikarijo, Iskra; Naumovska, Zorica; Petrovski, Ognen; Stavrikj, Katarina; Balkanov, Trajan (Scientific Foundation SPIROSKI, 2020)
BACKGROUND: The misuse and overuse of antibiotics contribute to the development of antimicrobial residence. Official data in EU/ EEA in 2017 in the hospital sector suggested that the consumption is lowest in the Netherlands, with 1 DDD per 1,000 inhabitants/day in comparison with Finland, with 2.8 DDD/TID. AIM: The aim of this study was to analyze data on the scope and structure of the antibiotic prescription in pediatric patients at University Children’s Hospital for period of 3 months in 2018 and 2019. MATERIALS AND METHODS: The data for antibiotic consumption were obtained from a hospital pharmacy, which are ordinated to hospitalized patients. RESULTS: The total amount of utilized antibacterial drugs with ATC code J01 for first quarter in 2018 is 33.65 DDD/100BD in comparison to the first quarter of 2019 when it declined to 32.09 DDD/100BD. The most consummated antibiotics in the first trimester of both years were the group of cephalosporins, especially the 3rd- and 4th-generation parenteral cephalosporins with from 16.96 to 19.25 DDD/100BD in the evaluated period. Decrease of penicillin’s, carbapenems, macrolides and quinolones were confirmed in the analyzed period. The most commonly used drugs remain ceftriaxone – 13.49 DDD/100BD in 2018 and increased to 14.41 DDD/100BD in 2019, followed by amikacin 3.21 DDD/100BD in 2018 and increased to 3.50 DDD/100BD in 2019 but azithromycin consumption significantly declined from 1.97 DDD/100BD to 0.81 DDD/100BD administered orally. The third most commonly utilized antibiotic in first quarter of 2019 become meropenem, antimicrobial drug from the group of carbapenems with 2.71 DDD/100BD. CONCLUSION: The benefits of monitoring the antibiotic prescribed pattern are critical due to the fact that they provide adequate data on consumption of antibiotics and adherence to guidelines.